Investigação de mutações nos genes sinápticos SHANK2 e SHANK3 em Transtornos do Espectro do Autismo - Rosan, Dante Bruno Avanso [UNESP] (2015)
The Autism Spectrum Disorders (ASD) are complex neuropsychiatric diseases, with widely etiology and clinical manifestations. Such manifestations are observed before three years of life. The prevalence is high in the population, with a ratio of four affected men for each affected woman. In only 10-25% of cases an etiological factor is observed, genetic or environmental, depending of the composition of samples and laboratory techniques used. There are descriptions of hundreds of genes and genomic regions associated with predisposition, they present mutations and copy number variations (CNVs) and most have expression in the central nervous system, especially at synapses. Among the candidate genes, we highlight the SHANK2 and the SHANK3, not yet studied in Brazilian subjects. In SHANK2, located in 11q13.2, mutations have been described in seven of its 25 exons, while in SHANK3 located at 22q13 with 23 exons, there are descriptions of mutations in several exons, but especially three. Many mutations in these two genes were observed in autistic patients, but not in healthy controls, suggesting an involvement in the etiology of the disease. This study investigated mutations in exons 11, 13 and 22 of SHANK2 gene and exons 2, 6 and 22 of SHANK3, which are most often involved in ASD findings. The study of six exons was performed by direct sequencing, in 200 affected and the results were compared to a genome bank with 566 healthy controls. Eleven alterations were found, six on SHANK2 gene, one not yet described, and five in SHANK3 gene, all not previously described. No patient had more than one alteration in SHANK2 or SHANK3, or both genes. The results showed that mutations in SHANK2 and SHANK3 gene are frequent in the Brazilian population with ASD and are related to the etiology of these diseases. However, the clinical relevance of each of the alterations found should be investigated. This study may help...